PENANAMAN NILAI MORAL DAN AGAMA MELALUI METODE BERCERITA PADA ANAK USIA DINI DI RA AL MUKHLISIN - Hanifah Syahputri; Susanti Nirmalasari; Nurhikmah Pohan; Armanila Armanila (HIBRUL ULAMA, 2025)
Early childhood education plays a crucial role in developing children's potential to prepare them for various life changes. One of the early childhood education institutions is Raudhatul Athfal (RA), which nurtures children aged 4-6 years in social-emotional, cognitive, language, physical-motor, religious, and artistic aspects. Moral and religious values are the primary focus before other developmental aspects, as children with noble character are more important than intelligence without morality. One of the teaching methods used to internalize moral and religious values is the storytelling method, which aims to encourage and guide children through questions that explore their ideas. Observations at RA Al Mukhlisin indicate that this method has successfully improved some children's moral and religious values, such as greeting others, apologizing, advising friends, and waiting in line. However, some children have yet to develop optimally despite receiving the same teaching methods.